An integrated multi-criteria analysis framework of built reservoir with dam-heightening-based decision: China's largest water transfer programs for sustainable development - Liu, Bin (2023)
An integrated multi-criteria analysis framework was proposed for the sustainable water management of built reservoir with dam-heightening-based decision, which enhances the conventional decision-making methods by more reasonably quantifying the decision-making process. The method utilizes a group of techniques involving game theory, analytic hierarchy process (AHP) identifying and considering different stakeholder groups, entropy weight, and fuzzy comprehensive evaluation (GAEF), and is applied to the largest water transfer programs in China. The study results showed that the improved multi-criteria decision framework can well deal with the decision-making problem of built reservoir construction scheme in facing the newly increased task of water transfer. The study identifies five stakeholders that affect the subjective weight of the heightening schemes of built reservoir for inter-basin water transfer. It was revealed that the game theory can better couple the collective wisdom of large complex groups and the objectivity of indicators than traditional methods such as geometric average. This study is of high reference value for the feasibility demonstration of built reservoir with dam-heightening-based decision around the world to achieve the water related Sustainable Development Goals (SDGs), especially for those reservoirs with water transferring tasks.